CBIO-20. HIGH LEVELS OF TERT CONFER SENSITIVITY TO THE DNA HYPOMETHYLATING AGENT DECITABINE (DAC) IN GLIOMAS. (12th November 2021) - Park, Jong-Whi; Sahm, Felix; Steffl, Bianca; Arrillaga-Romany, Isabel; Cahill, Daniel; Monje, Michelle; Herold-Mende, Christel; Wick, Wolfgang; Turcan, Sevin
Abstract: BACKGROUND: Decitabine (DAC)-incorporated DNA binds DNMT1 enzyme and subsequently triggers DNMT1 degradation. Previously, we showed that DAC can mediate the anti-tumor effect in a preclinical model of IDH-mutant gliomas. Here, we further investigate molecular determinants of response to DAC in gliomas. METHODS: DAC response was assessed by soft agar anchorage independent growth assays and cell proliferation measurements. Patient-derived IDH-mutant chromosome 1p/19q codeleted (codel) and non-codel glioma lines upon vehicle and DAC treatment were used for RNA sequencing and Gene Set Enrichment Analysis (GSEA). RESULTS: We found that DAC treatment is effective in high TERT-expressing gliomas including IDH-mutant and IDH-wildtype glioma lines. In contrast, pharmacological inhibition of TERT reduces DAC response in glioma lines. Interestingly, transcriptomic profiling showed that DAC reduces the expression of TERT, along with increased CDKN1A/p21 expression. We experimentally validated that TERT expression depends on CDKN1A/p21. Furthermore, p53 is required for DAC-mediated CDKN1A/p21 induction. Importantly, DAC-mediated proliferation defects in TERT-proficient glioma cells are abolished by DNMT1 knockdown, indicative of an expected DAC mechanism. CONCLUSIONS: DAC could elicit the pronounced anti-tumor response in IDH-mutant codel oligodendroglioma and IDH-wildtype glioblastoma with TERT activating mutations.